1997
DOI: 10.1677/jme.0.0190267
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the rat gene for the acid-labile subunit of the insulin-like growth factor binding protein complex

Abstract: The acid-labile subunit (ALS) of the ternary insulin-like growth factor-binding protein complex has a central role in controlling the bioavailability of circulating insulin-like growth factors. We have shown that gene expression of ALS is regulated by a number of factors, particularly growth hormone. Our aim was to characterize the ALS gene in order to define the mechanism of its regulation. Southern analysis suggests a single copy of the ALS gene in the rat genome. The protein-coding and 3 -untranslated regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…We previously showed that these effects of GH are transcriptional and mediated by STAT5 binding to a single GAS element in the proximal promoter of the mouse ALS gene (Ooi et al 1998). This GAS element is completely conserved in the promoter of the rat, sheep and human ALS gene (Delhanty & Baxter 1997, Rhoads et al 2000, Suwanichkul et al 2000. A similar mechanism has recently been shown to explain the positive effects of GH on the transcription of the rat IGF-I gene (Woelfle et al 2003, Chia et al 2006.…”
Section: Discussionmentioning
confidence: 77%
“…We previously showed that these effects of GH are transcriptional and mediated by STAT5 binding to a single GAS element in the proximal promoter of the mouse ALS gene (Ooi et al 1998). This GAS element is completely conserved in the promoter of the rat, sheep and human ALS gene (Delhanty & Baxter 1997, Rhoads et al 2000, Suwanichkul et al 2000. A similar mechanism has recently been shown to explain the positive effects of GH on the transcription of the rat IGF-I gene (Woelfle et al 2003, Chia et al 2006.…”
Section: Discussionmentioning
confidence: 77%
“…Using fluorescence in situ hybridization, the gene was mapped to bands A2-A3 of the mouse chromosome 17 [23]. This organization is identical to that of the rat and sheep ALS genes ( [24]; unpublished results).…”
Section: Organization Of the Mouse Als Genementioning
confidence: 86%
“…Mature mouse ALS is 92% identical to rat ALS, and 77% identical to human ALS [25,26]. It is organized into 18-20 leucine-rich domains of 24 amino acids each, which are thought to confer to ALS its ability to associate with the IGFBP-3:IGF binary complexes [23,24,26]. Mature mouse ALS contains 13 cys-563 teine residues, which occur at identical positions in rat ALS, and at 12 of 13 positions in human ALS [25,26].…”
Section: Organization Of the Mouse Als Genementioning
confidence: 99%
“…ALS and IGF-I are expressed predominantly in the liver, and their expression is regulated at the level of transcription by GH (12,23,39). Additionally, we have found that insulin modulates hepatic expression of ALS (17, 18).…”
mentioning
confidence: 94%